2013
DOI: 10.1007/s12471-013-0401-3
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent and founder mutations in the Netherlands—Phospholamban p.Arg14del mutation causes arrhythmogenic cardiomyopathy

Abstract: BackgroundRecently, we showed that the c.40_42delAGA (p.Arg14del) mutation in the phospholamban (PLN) gene can be identified in 10–15 % of Dutch patients with dilated cardiomyopathy or arrhythmogenic cardiomyopathy. The arrhythmogenic burden of the p.Arg14del mutation was illustrated by the high rate of appropriate ICD discharges and a positive family history for sudden cardiac death.MethodsOur goal was to evaluate the geographical distribution and the origin of this specific mutation in the Netherlands and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 35 publications
0
55
0
Order By: Relevance
“…We looked up the prevalence of this mutation in the database of the PREVEND study, which consisted of 8267 individuals recruited from the region where PLN-p.Arg14del is thought to have originated and where it is, therefore, expected to be most prevalent in the general population. 17,26 We found that PLN-R14del occurred significantly more often in ARREST than in PREVEND (0.56% versus 0.07%, Fisher's exact; P<0.0003, Table 2). …”
Section: Prevalence Of Founder Mutations In Arrest and Controlsmentioning
confidence: 72%
See 3 more Smart Citations
“…We looked up the prevalence of this mutation in the database of the PREVEND study, which consisted of 8267 individuals recruited from the region where PLN-p.Arg14del is thought to have originated and where it is, therefore, expected to be most prevalent in the general population. 17,26 We found that PLN-R14del occurred significantly more often in ARREST than in PREVEND (0.56% versus 0.07%, Fisher's exact; P<0.0003, Table 2). …”
Section: Prevalence Of Founder Mutations In Arrest and Controlsmentioning
confidence: 72%
“…[11][12][13][14][15] For instance, the PLN-p.Arg14del mutation, identified in 10% to 15% of Dutch patients with DCM or ARVC, is the most prevalent cardiomyopathy-associated mutation in the Netherlands. 17 Similarly, the MYBPC3-p. Trp792fsX17 mutation is found in 17% of hypertrophic cardiomyopathy index patients in the Netherlands. 27 Of note, besides their recurrence in patients with similar phenotypes, the pathogenicity of some of the mutations has also been demonstrated in functional studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 Similarly within Finland, 2 founder mutations account for as much as 18% of all hypertrophic cardiomyopathy in that population.…”
Section: Circ Cardiovasc Genetmentioning
confidence: 99%